2021
DOI: 10.3390/min11060552
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Calcium Oxalate/Sepiolite Composite for Highly Selective Adsorption of Pb(II) from Aqueous Solutions

Abstract: Synthesizing functional nanomaterials from naturally abundant clay has always been of vital importance for resource utilization, however, the lack of new methods to effectively utilize low-grade clay presents a significant challenge. Herein, a calcium oxalate/sepiolite nanocomposite (SMN-x) was prepared by using the water bath heating method to convert the associated calcium carbonate in low-grade sepiolite into calcium oxalate. The developed composite was subsequently used to remove Pb(II) from the aqueous so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…As shown in Figure 3a, the broadband around 3441 cm −1 is attributed to the stretching vibration of the terminal −OH and/or adsorbed water, [27] and the bands that appeared at 1619 cm −1 and 1425 cm −1 are due to the asymmetric and symmetric stretching vibration of −COOH, respectively [28–30] . By a careful comparing, it can be found that the vibration bands of −COO − (1610 cm −1 ) and the vibration bands of Si−O−Si located at around 1097, 805, and 472 cm −1 shift to lower wave number for the functional samples due to the influence of −NH 2 and −SH [31,32] . Furthermore, a new weak band around 2558 cm −1 belongs to the vibration of −SH appeared in the spectra of SH‐SiO 2 /SA [33] .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…As shown in Figure 3a, the broadband around 3441 cm −1 is attributed to the stretching vibration of the terminal −OH and/or adsorbed water, [27] and the bands that appeared at 1619 cm −1 and 1425 cm −1 are due to the asymmetric and symmetric stretching vibration of −COOH, respectively [28–30] . By a careful comparing, it can be found that the vibration bands of −COO − (1610 cm −1 ) and the vibration bands of Si−O−Si located at around 1097, 805, and 472 cm −1 shift to lower wave number for the functional samples due to the influence of −NH 2 and −SH [31,32] . Furthermore, a new weak band around 2558 cm −1 belongs to the vibration of −SH appeared in the spectra of SH‐SiO 2 /SA [33] .…”
Section: Resultsmentioning
confidence: 92%
“…[28][29][30] By a careful comparing, it can be found that the vibration bands of À COO À (1610 cm À 1 ) and the vibration bands of SiÀ OÀ Si located at around 1097, 805, and 472 cm À 1 shift to lower wave number for the functional samples due to the influence of À NH 2 and À SH. [31,32] Furthermore, a new weak band around 2558 cm À 1 belongs to the vibration of À SH appeared in the spectra of SH-SiO 2 /SA. [33] Therefore, it seems reasonable to believe that the synthesized materials had been successfully functionalized by -SH and -NH 2 groups.…”
Section: Characterization Of Adsorbentsmentioning
confidence: 99%
“…Furthermore, ζ potential indicates the surface charge and surface composition, which determine how particles grow and how adhesives and other particulates can be attached to particles. Hence, the ζ potential is important to make estimations on the electrochemical double layer forming around the particles and the resulting effects on adsorption of metal ions to the oxalate particles . The ζ potential is strongly dependent on the surface structure and composition and on the ionic strength of the solution .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the ζ potential is important to make estimations on the electrochemical double layer forming around the particles and the resulting effects on adsorption of metal ions to the oxalate particles. 53 The ζ potential is strongly dependent on the surface structure and composition and on the ionic strength of the solution. 54 In human kidneys, the ionic strength is usually isotonic and the pH is slightly acidic.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 As a pollution elimination strategy, the economic and ecological benefits of adsorption are an important index to evaluate the feasibility of the technology. Therefore, some cheap and environment-friendly natural minerals adsorbents such as carbonate, 10,11 Mg(OH) 2 /talc, 12 oxalate, 13 hydroxyapatite, 14 magnetic iron oxide, 15 alumina 16 and amorphous silicon dioxide 17 have attracted the attention. Among them, calcium carbonate has excellent adsorption performance for lead, but the carbonate is unstable under acidic conditions.…”
Section: Introductionmentioning
confidence: 99%